Functional and semantic appearances of ergonyms in modern Ukrainian language: for example of catering establishments in the city Kyiv - Vintoniv, Mykhailo; Vintoniv, Tatiana; Sydorenko , Olena (Skhid, 2024)
Proper names occupy an important place in any language, they quickly respond to various changes in society, reflect various historical, economic, social and ideological influences, change their semantic content due to changes in various aspects of cultural and historical development. The problem of collection, systematization and description of proper names arose in Ukrainian onomastics due to the sharp increase in their number at the end of the last century and needs to be organized and comprehensively studied. Ukrainian linguistic studies contain investigations of the ergonyms some regions. But the ergonyms of Kyiv are actively changing under the influence of extralinguistic factors and require special research. The material of this study includes 3,500 names of catering establishments fixed during 2022-2023 in Kyiv. The semantic manifestations of ergonyms of Kyiv for the designation of food establishments are analyzed in the article. The factors, contributing to the creation of such ergonyms are highlighted, the main structural and morphological features of such ergonyms are revealed. Special attention is paid to the sources and ways of borrowing of Kyiv’s ergonyms. The novelty of this study lies in the fact that for the first time ergonyms are considered as an element of the onomastic system and a unit of the onomastic space of Kyiv. A typology of ergonyms and their statistical description by structure and origin, including the fixation of graphics (Latinization, graphic deconstruction, etc.), is proposed.